BELAJAR MATERI PRISMA MENGGUNAKAN MODEL PEMBELAJARAN MATEMATIKA KOLB-KNISLEY - Samnufida, Rahmiliasari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— Problems encountered in the process of learning mathematics is that students have not been actively involved in the learning process and cause students to be passive because only teachers who are active therefore students only accept without them giving an opinion. The purpose of this research is to know how to learn the prism material using Kolb-Knisley's mathematical learning model. Kolb-Knisley learning model is a learning model developed by a person named Jeff Knisley which is based on Kolb model which Knisley assumes that this learning model happens to train students to be active because the learning process occurs turn of activeness between teachers and students. This model has four learning stages: Kongkrit-Reflective, Concrete-Active, Abstract-Active, And Reflective Abstract. Which happens change of activity between teacher and student so that learning will run well. Keywords: Kolb-Knisley's mathematical learning model. Abstrak— Permasalahan yang dihadapi dalam proses pembelajaran matematika adalah siswa belum terlibat aktif dalam proses pembelajaran dan menyebabkan siswa menjadi pasif karena hanya guru yang bersifat aktif oleh karena itu siswa hanya menerima tanpa mereka memberikan pendapat. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana belajar materi prisma menggunakan model pembelajaran matematika Kolb-Knisley. Model pembelajaran Kolb-Knisley merupakan model pembelajaran yang dikembangkan seseorang bernama Jeff Knisley yang didasari dari model Kolb yang mana Knisley beranggapan bahwa model pembelajaran ini terjadi melatih siswa menjadi aktif karena proses pembelajaran terjadi pergantian keaktifan antra guru dan siswa. Model ini memiliki empat tahap pembelajaran yaitu: Kongkrit-Reflektif, Konkrit-Aktif, Abstrak-Aktif, Dan Abstrak Reflektif. Yang mana terjadi pergantian keaktifan antara guru dan siswa sehingga pembelajaran akan berjalan dengan baik. Kata Kunci : Model pembelajaran matematika Kolb-Knisley.